VALUATION OF SAFETY APPLICATION OF LAND TRANSPORTATION ON PORONG ARTERIAL ROAD – PURWOSARI ROADWAY STA 30+00 – STA 61+400 - Umi Kulsum; Ibnu Sholichin (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Highways can have an impact on the social and economic development of the surrounding community as well as progress in the industrial sector. Road safety is an important aspect that must be considered. The main problem that often occurs in these accidents apart from human factors can also be caused by road infrastructure. Along Porong Arterial Road – Roadway Purwosari STA 30+00 – 61+400 in certain locations along the road there are inadequate road completeness facilities such as PJU lights that do not turn on or PJU distances that are too far away, pavement damage and road markings less clear. Based on these field conditions, it is necessary to evaluate traffic safety based on the main attributes that must be repaired using the Importance Performance Analysis method, namely the street lights are on well, damaged roads have been replaced/repaired and roads are free from damage such as waves, potholes. and puddles. According to the weighting with the EAN (Equivalent Accident Number) method based on data from the Police Resort of Sidoarjo Regency and Pasuruan Regency in 2016 - 2020 it was 486, located at STA 38+00 – 39+00 with a total of 590 cases. The blackspot point is located at the Apolo Roundabout with (R analysis) > (R Existing) = 30 m > 18.03 concluded that it does not meet the standards and the value of side freedom and (E analysis) < (E existing) = 5m < 7 m is concluded to have met the standard.